(untitled) (World Economics and Finance Bulletin, 2025)
This article analyzes population growth and the labor market, as well as their impact on economic development. Various theoretical approaches, particularly the views of Malthus, Keynes, Becker, and Piketty, are examined to highlight both the positive and negative aspects of demographic growth. Methodologically, a mixed-method approach is employed, using statistical data from Uzbekistan for the period of 2013–2023. The analysis shows that while population growth has contributed to the increase in labor resources and GDP volume, employment rates have demonstrated varying dynamics. Furthermore, it is emphasized that economic growth is not solely driven by population increase, but is also closely linked to factors such as productivity, technological advancement, and investment.